THE CONSUMER ACCEPTANCE ON SEAWEED JELLY CANDY (Gracilaria sp) WITH ADDITION OFBEET (Beta vulgaris L.) EXTRACTASNATURAL DYE MATERIAL - Liza Mulya Sari; Mery Sukmiwati; Sumarto Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This study aimed to determine the consumer acceptance of seaweed jelly candy (Gracilaria sp) with the addition of beet extract as a natural dye, and to knowthe optimum concentrationof the extract of the beet in the best jelly candy preferred by consumers. The research method used is experimental by using non factorial complete random design. The treatment conducted was the addition of beet extract at different concentrations(0, 20, 40, and 60 %) The results showed that the addition of beet extracts affected significantly on the organoleptic valueof seaweed jelly candy. Itwas indicated that the addition of beet extract 40% is the best treatment in producing seaweed jelly candy. The characteristics of the best seaweed jelly candy were red colored, fine fibrous and chewy textured, had the beet and seaweed aroma, and the typical sweet taste of beets. This seaweed jelly candy added with beet extract 40% cantained 19.68% water, 3.30%protein, and 7.85% sugar reduction. Keywords:Beta vulgaris L, Extract,Gracilaria sp,Jelly candy.